Hemangiosarcoma in The Golden Retriever - Dhirgo Adji (Jurnal Sain Veteriner, 2012)
A Golden retriever dog, male, 9 years old was a patient of Surgery Clinic, Department of Surgery and Radiology, Faculty of Veterinary Medicine, Gadjah Mada University. The patient was dated on September 27, 2012. Clinically observation showed skinny, normal appetite, and not showing any physiologic change except that there were superficially bumps on the inguinal skin 4 cm in diameter size. The tumor biopsy was performed using lidocaine 2% as local anaesthetic circullary application. Histopathologically analysis of the tumor tissue was identified as hemangiosarcoma.